2011
DOI: 10.1111/j.1751-553x.2011.01371.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of hemoglobin Constant Spring in heterozygote and homozygote by a capillary electrophoresis method

Abstract: CE is the preferable method for screening of heterozygote and homozygote of Hb CS. Moreover, in conjunction with a lower MCV (<70 fL), this approach provided a high resolution to identify Hb H-CS disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The corrected Hb CS levels could be used for screening of heterozygote or homozygote for Hb CS. Consistency with the previous study indicated that the level of Hb CS quantified by CE proved useful in screening of heterozygote and homozygote for Hb CS [9]. In conclusion, the co-inheritance of Hb Hope and heterozygote or homozygote for Hb CS can be found in the Thai population.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The corrected Hb CS levels could be used for screening of heterozygote or homozygote for Hb CS. Consistency with the previous study indicated that the level of Hb CS quantified by CE proved useful in screening of heterozygote and homozygote for Hb CS [9]. In conclusion, the co-inheritance of Hb Hope and heterozygote or homozygote for Hb CS can be found in the Thai population.…”
Section: Discussionsupporting
confidence: 86%
“…The a-thalassemia-1 SEA and Thai type deletions were detected by using realtime PCR with SYBR Green1 high resolution melting (HRM) analysis as previously described [8]. Moreover, the molecular confirmation tests for Hb Hope and Hb CS were performed by using the amplification refractory mutation system (ARMS)-PCR analysis as reported elsewhere [6,9].…”
Section: Molecular Analysis For Diagnosis Of Thalassemia and Hemoglobmentioning
confidence: 99%
“…The levels of Hb CS in the groups with b-thal trait and Hb E trait varied from 0.1-2.8 and 0.1-2.3%, respectively (Table 1). Two cases had Hb CS levels higher than 2.0%, thus, they were subjected to ARMS analysis (17) in order to provide a rapid molecular diagnosis of heterozygous and homozygous Hb CS. The amplified fragments from the Hb CS allele with the 180 bp but not from a normal allele were observed (data not shown), indicating that these two samples were Hb CS homozygotes.…”
mentioning
confidence: 99%
“…However, the degraded HbCS peak was not found on CE eletropherogram of the fresh whole blood of these samples. Therefore, the lyophilized Hb typing control material should be prepared from the blood samples of homozygous of HbCS or HbH-CS disease which contain a high level of HbCS than those of heterozygous HbCS [19]. The most common adult Hb is HbA (95%) which consists of 2 α-and 2 β-globin chains (α 2 β 2 ) and their production being governed by four α-genes (2 α1-genes and 2 α2-genes) and two β-genes, respectively [20].…”
Section: Discussionmentioning
confidence: 99%